The Cross Talk Between p53 and mTOR Pathways in Response to Physiological and Genotoxic Stresses - Cui, Danrui; Qu, Ruirui; Liu, Dian; Xiong, Xiufang; Liang, Tingbo; Zhao, Yongchao (Frontiers in Cell and Developmental Biology, 2021)
The tumor suppressor p53 is activated upon multiple cellular stresses, including DNA damage, oncogene activation, ribosomal stress, and hypoxia, to induce cell cycle arrest, apoptosis, and senescence. Mammalian target of rapamycin (mTOR), an evolutionarily conserved serine/threonine protein kinase, serves as a central regulator of cell growth, proliferation, and survival by coordinating nutrients, energy, growth factors, and oxygen levels. p53 dysfunction and mTOR pathway hyperactivation are hallmarks of human cancer. The balance between response to stresses or commitment to cell proliferation and survival is governed by various regulatory loops between the p53 and mTOR pathways. In this review, we first briefly introduce the tumor suppressor p53 and then describe the upstream regulators and downstream effectors of the mTOR pathway. Next, we discuss the role of p53 in regulating the mTOR pathway through its transcriptional and non-transcriptional effects. We further describe the complicated role of the mTOR pathway in modulating p53 activity. Finally, we discuss the current knowledge and future perspectives on the coordinated regulation of the p53 and mTOR pathways.